Visible-Light-Induced Three-Component Radical Coupling of Selenocarbamates, Enones, and Allylstannanes with Diphenyl (2,4,6-trimethylbenzoyl)phosphine Oxide - Komine, Keita; Yamazaki, Yuta; Iwanaga, Taiga; Sakaguchi, Hikaru; Fukuda, Hayato; Ishihara, Jun (Synlett, 2023)
A blue LED-induced three-component coupling of a carbamoyl radical, cyclic enone, and allylstannane was developed. The use of blue LEDs and diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide (TPO) as a radical initiator permitted the three-component radical coupling to proceed with a high chemoselectivity. An elucidation of the mechanism revealed a pathway for the formation of a tributyltin radical from TPO and allylstannane. This tandem radical reaction is expected to be applicable in natural-product synthesis.
Keywords: radical reaction; coupling; multicomponent reaction; photochemical reaction; total synthesis; amides